Տարտանելի առասպելը կամ ռազմավարական PR–ի թուրքական «Սև խոռոչը» - Շիրինյան, Լևոն (Զանգակ հրատ.)
В документе представлены воспоминания и оценки Вегиб паши –турецкого военно– политического деятеля времен Первой мировой войны – о событиях вокруг «турецких морских путей» в контексте всемирной политической игры. В рассуждениях автора явно просматривается безошибочно действующая в природе и обществе закономерность – постоянное стремление к равновесию, приносящее одним смерть, другим – счастье, хотя и временное. In the context of the hundredth anniversary of the First World War, the recognition of “Armenocide” by Turkey is significant sometimes for revealing the historical truth, and in some ways for refirming the chain of lies and disguising crucial historical facts. Among those events it is worth mentioning the desire of France and England to conquer “Turkish water routs’, the motivation of some influential countries and the victory of Turkey.
Keywords: Գիտնականի մտորումներ; Քաղաքականություն